2018
DOI: 10.1177/1367493518764337
|View full text |Cite
|
Sign up to set email alerts
|

Parental Stress Scale: Validation study with a Portuguese population of parents of children from 3 to 10 years old

Abstract: The aim of this study was to validate the Parental Stress Scale (PSS) for Portuguese parents and to further investigate the scale's criterion-related validity. A two-stage stratified sample of the Portuguese population of parents, with children attending public preschools and primary schools, was obtained, totalizing 3842 parents of children between 3 and 10 years old. Parents completed a Parental Concerns Scale and the Portuguese version of the PSS. Results support the four-factor structure of the Portuguese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(65 citation statements)
references
References 37 publications
6
40
0
11
Order By: Relevance
“…Lastly, only two studies [19,29] have investigated whether PSS items were more strongly correlated that could be explained by the constructs measured (i.e. items are locally dependent), and both found this not to be the case for items 1 and 17, and one of the studies also for items 3, 4, 9, 10, 12, 16 and 18 (Additional file 1: Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, only two studies [19,29] have investigated whether PSS items were more strongly correlated that could be explained by the constructs measured (i.e. items are locally dependent), and both found this not to be the case for items 1 and 17, and one of the studies also for items 3, 4, 9, 10, 12, 16 and 18 (Additional file 1: Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Berry and Jones [1] originally reported that the full PSS had adequate reliability (Cronbach's alpha = .83) as well as adequate reliability over time (test-retest correlation = .81 over 6 weeks) Other studies [19,28,30,37,38] have reported corresponding reliability results for different language versions with Cronbach's alpha ranging from .73 [27] to .90 [30] for the full PSS. The studies that report reliability for the two PSS dimensions separately find varying levels of reliability for both the parental stress dimension (.64-.71 [29]; .76 [26]; and .79 [27]) and the parental satisfaction dimension (.61 [29]; .77 [26]; and .69 [27]).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 40 years of parenting research, several measures have been developed that purport to assess the impact of parenting on parents and carers (Louie et al, 2017). The Parenting Stress Index (PSI; Abidin, 1995) was developed and has been used extensively to measure perceived stress specific to the parenting role (Algarvio et al, 2018;Cheung, 2000;Lessenberry & Rehfeldt, 2004) and purportedly measures the impact of stress in the parent-child system. It also has been used extensively with children from clinical populations as a predictor of cognitive and behavioural problems (Aracena et al, 2016).…”
Section: Assessing Positive and Negative Aspects Of Parentingmentioning
confidence: 99%
“…Therefore, PSS items were designed to reflect these two dimensions with positive emotion, sense of fulfillment, and satisfaction with the parenting role alongside stressful elements such as demands on time, energy, self-esteem, and control (Berry & Jones, 1995;Louie et al, 2017;Zelman & Ferro, 2018). The developers proposed that the total PSS score represents the balance between the positive and negative aspects of parenting (Algarvio et al, 2018;Lessenberry & Rehfeldt, 2004). However, an approach that collapses scores across the two subscales loses important information about the complexities of the caregiver role.…”
Section: Assessing Positive and Negative Aspects Of Parentingmentioning
confidence: 99%
See 1 more Smart Citation